Transcatheter aortic valve implantation with the Edwards Sapien 3 valve: First experiences in Turkey - Abdullah Nabi Aslan; Serdal Baştuğ; Hacı Ahmet Kasapkara; Hüseyin Ayhan; Hakan Süygün; Telat Keleş; Tahir Durmaz; Nihal Akar Bayram; Emine Bilen; Engin Bozkurt (KARE Publishing, 2016)
Objective: Transcatheter aortic valve implantation (TAVI) has shown promising results in patients with severe aortic stenosis (AS) at high risk for open heart surgery. We aimed to evaluate outcomes of patients who underwent TAVI with Edwards SAPIEN 3 Transcatheter Heart Valve (S3), a second-generation TAVI device. Methods: Between November 2014 and June 2016, 31 high-risk patients received balloon-expandable S3 valve at Atatürk Training and Research Hospital that has the largest case series in Turkey. Results: Mean age of the patients was 76.1+-12.6 years. Mean Society of Thoracic Surgeons and logistic European System for Cardiac Operative Risk Evaluation scores were 7.8%+-3.1 and 31.4%+-17.6, respectively. S3 valve was implanted in 27 patients via transfemoral approach and via trans-subclavian approach in 4 patients under local (n=29) or general (n=2) anesthesia. Procedural success rate was 100% (23 mm, n=7; 26 mm, n=16; 29 mm, n=8). Paravalvular aortic regurgitation (PAR) was absent or trivial in 29 (93.6%) patients and mild in 2 (6.4%) patients. Permanent pacemaker implantation (PPI) was required in 2 (6.4%) patients during the procedure, and in-hospital mortality occurred in 1 (3.2%) of those 2 patients. Conclusion: S3 valve is associated with higher rate of device success and lower incidence of PAR, peripheral vascular complications, and need for new PPI.